Could recent advances and new perspectives in science education and conceptual change improve public understanding of science? - Potvin, Patrice; Bélanger, Michel (Frontiers in Communication, 2024)
This perspective article explores the intersection of science education advancements and public science understanding improvement efforts, critiquing the still prevalent “deficit model” of science communication. It argues for a nuanced approach, incorporating insights from conceptual change research and the coexistence of scientific and misconceived notions within learners. Highlighting the prospects and promises of representational pluralism, it suggests strategies for science communicators to foster public engagement, emphasizing the importance of young audiences, avoiding simplistic dichotomies, and promoting critical thinking. The piece advocates for mutual enrichment between science education and communication, aiming for a well-informed, epistemologically competent public capable of navigating the complexities of scientific discourse.